2021
DOI: 10.3233/cbm-210061
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ISG20 predicts a poor prognosis in acute myeloid leukemia

Abstract: BACKGROUND: Acute myeloid leukemia (AML) is one of the most malignant hematopoietic system diseases. Interferon stimulated exonuclease gene 20 (ISG20) is a protein induced by interferons or double-stranded RNA, which is associated with poor prognosis in several malignant tumors. However its expression in AML is unknown. OBJECTIVE: To explore the expression of ISG20 in AML and its prognostic significance. METHODS: The expression of ISG20 in AML patients was analyzed by GEPIA database, detected by qRT-PCR and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…ISG20 level has been reported to be overexpressed in 65.9% (145 out of 220) cancerous tissues compared to concordant adjacent tissues in analyzes with databases [37]. While supporting the progression of the disease [16,38,39], high expression in AML is an indicator of poor prognosis [40]. We found that the expression of ISG20 mRNA was signi cantly increased in MM than the control group.…”
Section: Discussionmentioning
confidence: 60%
“…ISG20 level has been reported to be overexpressed in 65.9% (145 out of 220) cancerous tissues compared to concordant adjacent tissues in analyzes with databases [37]. While supporting the progression of the disease [16,38,39], high expression in AML is an indicator of poor prognosis [40]. We found that the expression of ISG20 mRNA was signi cantly increased in MM than the control group.…”
Section: Discussionmentioning
confidence: 60%
“…ISG20 can cleave single-stranded RNA or DNA and is significantly associated with host antiviral innate immune defense [ 12 , 13 ]. Several reports also suggest a link between ISG20 and the tumorigenic process of multiple neoplasms, including glioma [ 14 ], oral tumor [ 15 ], clear cell renal cell carcinoma [ 16 ], hepatocellular carcinoma [ 17 ], breast cancer [ 18 ], and acute myeloid leukemia [ 19 ], although the exact ISG20 pathomechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%